Infection prevention and control compliance among nurses and nursing students during COVID-19 in Malaysia - Abdul Hamid, Siti Hazariah; Hasan, Haliza; Mamat, Wan Hasliza Wan; Ho, Dina Syazana Ho Imran; Hasan, Muhammad Kamil Che (Intelektual Pustaka Media Utama, 2024)
The Malaysian COVID-19 hospital admission rate and the intensive care wards usage are now declining as the health service system enters a stage of recovery in the endemic phase. This study aimed to explore the barriers to and facilitators of infection prevention and control (IPC) compliance among staff nurses and nursing students and to observe their IPC compliance when attending to the patients in the respective wards. Qualitative study using in-depth interviews was conducted with staff nurses and the nursing students as primary data collection methods and supported with direct observation in the wards. A total of 21 staff nurses and 14 undergraduate nursing students from multiple wards were purposively sampled from April to December 2022. Data were analyzed using thematic analysis in Nvivo software. Four key themes were emerged in this study such as the partcipants i) Narrating IPC compliance; ii) IPC compliance adherence; iii) Perceived barriers for noncompliance to IPC; iv) Empowering staff nurses and nursing students on IPC compliance. The study findings served as key evidence for the hospital top management and the nursing faculty in planning the strategies to improve the IPC training and monitoring by empowering staff nurses and nursing students at their teaching hospitals.